Pengaruh Tax Amnesty dan Kondisi Keuangan pada Tingkat Kepatuhan Wajib Pajak Orang Pribadi - Vio Narakusuma Ardayani, Putu; Jati, I Ketut (E-Jurnal Akuntansi; Vol 26 No 3 (2019), 2019)
This study aims to determine the effect of tax amnesty and financial conditions on the level of individual taxpayer compliance registered at the East Denpasar Primary Tax Office. The population in this study was 38,647 individual taxpayers registered in East Denpasar Primary Tax Office in 2017. The respondents of this study were 100 individual taxpayers registered at the East Denpasar KPP Pratama. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that tax amnesty and financial conditions have a positive effect on the level of individual taxpayer compliance. The results of this study are expected to be able to provide references, input and additional information for relevant parties, especially the government (DGT) so that in the future the results of this study can help decision making process in order to increase the level of individual taxpayer compliance. Keywords: Tax amnesty, financial condition, taxpayer compliance